(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to assess the effect of acibenzolar-s-methyl, potassium phosphite, potassium silicate, and trifloxystrobin + prothioconazole products on curative control of powdery mildew (Microsphaera diffusa) in soybean. The experimental design was completely randomized, in a single factor scheme, containing five treatments with four replications. The products were applied on leaves at the V4 phenological stage, with disease severity of 5%. At 7, 14, and 21 days after the application of the products (DAA), the incidence and severity of the disease were assessed. The trifloxystrobin + prothioconazole reduced by 30% the disease incidence and 80% disease severity compared to the control. The inhibitory effect of the products on conidia production in vivo and its germination in vitro were also assessed. Trifloxystrobin + prothioconazole was more effective in the reduction of both conidia production and germination. Acibenzolar-s-methyl, potassium phosphite, and potassium silicate reduced conidia germination, but neither affected the disease severity nor the conidia production. Based on this, it can be concluded that the fungicide trifloxystrobin + prothioconazole reduced the production of conidia and inhibited its germination, showing curative and protective effect against soybean powdery mildew and that the resistance inducers tested interfered with pathogen germination, but without significant effect on the disease when applied after the onset of symptoms.